2005
DOI: 10.1590/s0100-879x2005000400006
|View full text |Cite
|
Sign up to set email alerts
|

APOA1/C3/A4 gene cluster variability and lipid levels in Brazilian children

Abstract: Genetic studies have suggested that polymorphisms of genes coding for apolipoproteins are significant determinants of serum lipoprotein and lipid levels in adults. However, only a few studies have investigated the association of these polymorphisms in children. Therefore, in the present investigation we studied the distribution of APOA1 -75 G>A, +83 C>T, APOC3 -482 C>T, -455 T>C and 3238 C>G, and APOA4 Q360H and T347S polymorphisms and their influence on plasma lipoprotein levels in children from a Brazilian n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
(22 reference statements)
0
10
1
2
Order By: Relevance
“…In a study of Hispanic and non-Hispanic white nuclear families, a significant association between triglyceride levels and the APOC3 À455 T/C polymorphism was found only in adults, although in analyses combining generations, there were no significant interactions between parent/child status and genotype [31]. A study of APOA1/C3/A4 polymorphisms in Brazilian children 5 to 15 years of age found no variants associated with triglyceride levels, but the polymorphisms differed from those in the present study [32].…”
Section: Discussioncontrasting
confidence: 76%
“…In a study of Hispanic and non-Hispanic white nuclear families, a significant association between triglyceride levels and the APOC3 À455 T/C polymorphism was found only in adults, although in analyses combining generations, there were no significant interactions between parent/child status and genotype [31]. A study of APOA1/C3/A4 polymorphisms in Brazilian children 5 to 15 years of age found no variants associated with triglyceride levels, but the polymorphisms differed from those in the present study [32].…”
Section: Discussioncontrasting
confidence: 76%
“…Genotyping was carried out using a previously reported protocol (De França et al, 2005). Data are reported as means ± SD.…”
Section: Methodsmentioning
confidence: 99%
“…The human genes APO A1 and APO A4 are arranged in tandem in a 17kb deoxyribonucleic acid segment on the long arm of chromosome 11 [32]. APO A1 is synthesized in the liver and it is the major component of the HDL, playing a role in reverse cholesterol transport from peripheral tissues to the liver [33]. APO C3, a major component of TG-rich lipoproteins (VLDL and CM) and a minor component of HDL, is synthesized predominantly in the liver and in a smaller extent in the intestine [34].…”
Section: Polymorphisms In Apolipoprotein Genesmentioning
confidence: 99%
“…APO C3, a major component of TG-rich lipoproteins (VLDL and CM) and a minor component of HDL, is synthesized predominantly in the liver and in a smaller extent in the intestine [34]. Its main function is still unknown [33].…”
Section: Polymorphisms In Apolipoprotein Genesmentioning
confidence: 99%
See 1 more Smart Citation